An Aluminum Fluoride Complex with an Appended Ammonium Salt as an Exceptionally Active Cooperative Catalyst for the Asymmetric Carboxycyanation of Aldehydes. Issue 14 (1st March 2017) - Brodbeck, Daniel; Broghammer, Florian; Meisner, Jan; Klepp, Julian; Garnier, Delphine; Frey, Wolfgang; Kästner, Johannes; Peters, René
Abstract: Al−F bonds are among the most stable σ bonds known, exhibiting an even higher bond energy than Si−F bonds. Despite a stability advantage and a potentially high Lewis acidity of Al−F complexes, they have not been described as structurally defined catalysts for enantioselective reactions. We show that Al−F salen complexes with appended ammonium moieties give exceptional catalytic activity in asymmetric carboxycyanations. In addition to aromatic aldehydes, enal and aliphatic substrates are well accepted. Turnover numbers up to around 10 4 were achieved, whereas with previous catalysts 10 1 –10 2 turnovers were typically attained. In contrast to Al−Me and Al−Cl salen complexes, the analogous Al−F species are remarkably stable towards air, water, and heat, and can be recovered unchanged after catalysis. They possess a considerably increased Lewis acidity as shown by DFT calculations. Abstract : AlF has landed : In comparison to its Al−Me and Al−Cl analogues, a structurally defined Al−F complex is unusually stable towards air, moisture, and heat, probably as a result of the very strong Al−F bond. In asymmetric carboxycyanations, the Al−F complex shows extraordinary catalytic activity.